Characteristics and risk factors of isolated and quarantined children and adolescents during the first wave of SARS-CoV-2 pandemic: A cross-sectional study in Modena, Northern Italy: SARS-CoV-2 in Modena children - Paduano, Stefania; Facchini, Maria Chiara; Greco, Antonella; Borsari, Lucia; Mingrone, Valentina M.; Tancredi, Stefano; Fioretti, Elisabetta; Creola, Giacomo; Iacuzio, Laura; Casaletti, Giovanni; Vinceti, Marco; Bargellini, Annalisa; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: In early 2020, SARS-CoV-2 was declared a pandemic by the WHO and Italy was one of the first and most severely affected country in Europe. Despite the global interest about COVID-19 pandemic, several aspects of this infection are still unclear, especially in pediatric population. This study aims to investigate the characteristics of the isolated or quarantined children and adolescents followed by the Public Health Department of the Italian province of Modena during the first wave of COVID-19.Methods: The study population included all non-adult subjects aged 0-18 years who underwent isolation or quarantine during the first wave of SARS-CoV-2 pandemic from February 24 to June 18, 2020 in Modena province, Northern Italy.Results: In Modena province, 1230 children and adolescents were isolated in case of SARS-CoV-2 infection (6.3%), or quarantined due to close contact with confirmed cases (88.7%) or travelling from a high-risk area (5.0%). Among 349 individuals who underwent swab testing, 294 (84.2%) reported close contact with an infected cohabiting relative and 158 (45.3%) were symptomatic. Among all tested subjects, 78 (22.4%) resulted positive, with a higher proportion of symptomatic subjects compared with the SARS-CoV-2-negative (78.2% vs. 35.8%). Fever was mostly present in SARS-CoV-2-positive children (48.7% vs. 12.6%). Both anosmia (58.3% vs. 41.7%) and dysgeusia (54.5% vs. 45.5%) had only slightly higher frequency in SARS-CoV-2-positive.Conclusions: These findings allow to expand the knowledge regarding characteristics of non-adult subjects isolated or quarantined during the first wave of SARS-CoV-2 pandemic. (www.actabiomedica.it)